2015
DOI: 10.1063/1.4918887
|View full text |Cite
|
Sign up to set email alerts
|

Weld lines in extrusion: Understanding the role of the flow conditions

Abstract: The effect of extrusion operating conditions on the on-line apparent viscosity of 98% Amylopectin (Amioca) and 70% Amylose (Hylon 7) corn starches during extrusion Abstract. This work presents a numerical and experimental study on the flow behavior of a polymer melt around the spider leg of a prototype extrusion die, designed to study the relationship between the thermo-mechanical conditions in which the weld lines are formed and their impact. The numerical simulations will enable to study the influence of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 18 publications
(38 reference statements)
0
9
0
Order By: Relevance
“…The authors compared the performance of the non-linear Simplex method with a trialand-error procedure, but no conclusion about the best method was clearly reported [151]. The optimization results were assessed experimentally [152,153]. Zhang et al [154] applied a gradient method based on a sensitivity analysis of a response surface obtained from 3D numerical modelling relating the objective function with the design variables, to optimize an L-shape profile die.…”
Section: Mandrel Diesmentioning
confidence: 99%
“…The authors compared the performance of the non-linear Simplex method with a trialand-error procedure, but no conclusion about the best method was clearly reported [151]. The optimization results were assessed experimentally [152,153]. Zhang et al [154] applied a gradient method based on a sensitivity analysis of a response surface obtained from 3D numerical modelling relating the objective function with the design variables, to optimize an L-shape profile die.…”
Section: Mandrel Diesmentioning
confidence: 99%
“…Since the FMM has four model parameters, it is expected to provide additional flexibility in fitting a wider range of complex fluid rheology, particularly for complex fluids such as biopolymer gels for which the zero shear viscosity is indeed unbounded. In order to test this, we have performed a fit with a Maxwell model and both FMM and FVF to the experimental data (G and G ) obtained from the rheological characterisation (Small Amplitude Oscillatory Shear at 230 • C) of a polystyrene extrusion grade, Polystyrol 158K from BASF [56], and the experimental data obtained for the xanthan gum with a concentration of 0.25 wt.% [26] (presented before).…”
Section: Infinite Parallel-series Combination Of Springs and Dashpotsmentioning
confidence: 99%
“…When melt flow fronts with such 'skin' meet each other and form weld lines, the actual contact part is the 'skin' of the melt flow fronts which have been cooled in some degree and partially solidified, even there may be a portion of the air encapsulated between the contact surfaces. This kind of weld lines greatly reduce the strength of polymer melt joints and seriously affect the mechanical properties of plastic parts [24,25]. In order to understand the influence of weld lines on the mechanical properties of plastic parts and reduce their adverse influence, researchers have done a lot of research through experiments or simulation methods.…”
Section: Introductionmentioning
confidence: 99%
“…In order to understand the influence of weld lines on the mechanical properties of plastic parts and reduce their adverse influence, researchers have done a lot of research through experiments or simulation methods. Carneiro et al [25] simulated and analyzed the flow behavior of polymer melt in extrusion die with splitter bridge during the weld line formation process and studied the flow type of melt and corresponding stress of splitter bridge position by using Giesekus model and the extended version of OpenFOAM under the assumption of isothermal flow of polymer melt during the whole weld line formation process. The results showed that higher temperature and pressure can improve the mechanical properties of extruded polymers with weld lines.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation